Market Manifestation of Nonpublic Information Prior to Mergers: The Effect of Ownership Structures. - Haw, In-Mu; Pastena, Victor S. (The Accounting Review, 1990)
Abstract Studies the effects of the disclosure of nonpublic information to explain target firms' runups prior to mergers. Criticisms on the disclosure system; US Securities and Exchange Commission's disclosure laws; Effects of ownership control structure on the dissemination of firms' acquisition-related information.